2013
DOI: 10.7197/1305-0028.2021
|View full text |Cite
|
Sign up to set email alerts
|

Acil servise ateş nedeni ile yapılan başvuruların değerlendirilmesi: Bir üniversite hastanesi tecrübesi

Abstract: Amaç. Bu çalışmanın amacı, Akdeniz iklimi etkisi altında olan Kuzey Kıbrıs'ta ortaya çıkan ateşli hastalıklar ve hastaların yakınmaları arasındaki ilişkinin araştırılmasıdır. Üniversite hastanesi acil servisine ateş nedeni ile başvuran hastaların başvuru yakınmaları ve etiyolojilerinin epidemiyolojik açıdan değerlendirilmesidir. Yöntem. Retrospektif olarak Temmuz 2010 ile Temmuz 2012 tarihleri arasında Kuzey Kıbrıs Türk Cumhuriyetindeki (KKTC) Tıp Fakültesi Hastanesi acil servisine başvuran hastaların başvuru … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…In their study, Süer et al 5 found that the most common reason for admission to the emergency department in patients with high fever was sore throat, with a rate of 29.3%. When the reasons for admission of the pediatric age group with high fever were examined, the most common reason was found to be sore throat.…”
Section: Discussionmentioning
confidence: 95%
“…In their study, Süer et al 5 found that the most common reason for admission to the emergency department in patients with high fever was sore throat, with a rate of 29.3%. When the reasons for admission of the pediatric age group with high fever were examined, the most common reason was found to be sore throat.…”
Section: Discussionmentioning
confidence: 95%